(untitled) (Acta Scientiarum. Biological Sciences, 2019)
Lipases (E.C. 3.1.1.3) are serine-hydrolases, and act on long chain fatty acid ester bonds. They exhibit specific and enantioselective activities, which are desirable for many industrial applications. This study aimed at screening and optimizing the production of lipases by wild yeast strains from a variety of substrates, as well as characterizing the enzyme. An initial selection was made in oxygenated oil-supplemented minimum medium, and the enzymatic activity of the supernatant was tested over p- nitrophenyl palmitate. One-hundred and twenty-four yeast strains from different substrates were tested, and twenty-three showed significantly higher lipolytic activity (p <0.01). One yeast in particular, QU110, showed best lipase production and therefore was selected for the optimization and characterization processes. This yeast exhibits enzyme secretion in initial pH 6.0, with olive oil and tryptone as carbon and nitrogen sources, respectively. There was a strong interaction between nitrogen source and initial pH, and pH 9.0 seems to inhibit enzyme secretion. The crude enzyme (cell-free supernatant) shows stability in surfactants and n-hexane, but not in ethanol or methanol. A Response Surface Model was created and optimal enzyme activity conditions were observed at 36°C and pH 8.0. The lipase is appropriate for transesterification reactions, as the enzyme is more stable in strong apolar solvents than moderately apolar ones. Also, secretion by pH was not reported elsewhere, which should be further investigated and contribute for other yeast bioprocesses as well.